Cross-contamination of Escherichia coli O157:H7 and Listeria monocytogenes in the viable but non-culturable (VBNC) state during washing of leafy greens and the revival during shelf-life. (February 2023) - Truchado, Pilar; Gómez-Galindo, Marisa; Gil, M.I.; Allende, Ana
Abstract: Some water disinfection treatments, such as chlorine and chlorine dioxide, used in the fresh-cut industry to maintain the microbiological quality of process water (PW), inactivate bacterial cells in the water but they also lead to the induction of an intermediate state between viable and non-viable known as viable but non-culturable (VBNC) state. Viable cells can participate in cross-contamination events but the significance of VBNC cells in PW, transfer to the product and potential resuscitation capacity during storage is unclear. The present study aims to determine first, if VBNC cells present in PW can cross-contaminate leafy greens during washing and secondly its potential revival during shelf-life. Process water characterized by a high chemical oxygen demand, due to the presence of high levels of organic matter, was inoculated with Listeria monocytogenes or Escherichia coli O157:H7. Inoculated PW was then treated for 1 min with chlorine dioxide (3 mg/L) or chlorine (5 mg/L) to generate VBNC cells. Absence of culturable cells was confirmed by plate count and VBNC cells by viability quantitative polymerase chain reaction (v-qPCR) complemented with two dyes, ethidium (EMA) and propidium (PMAxx) monoazide. Cross-contamination of shredded lettuce was demonstrated by monitoring the VBNC cells after washing the product for 1 min in the contaminated PW and during shelf life (15 days at 7 °C). In the case of L. monocytogenes, considering the total concentration of L. monocytogenes VBNC cells present in the PW, only a low proportion of cells were able to cross-contaminate the product during washing. VBNC L. monocytogenes cells were able to resuscitate on the product during shelf life, although levels of cultivable bacteria, close to the limit if detection (0.7 ± 0.0 log CFU/g), were only detected at the end of storage. On the other hand, VBNC cells of E. coli O157:H7 present in PW were not able to cross-contaminate shredded lettuce during washing. Moreover, when shredded lettuce was artificially inoculated with VBNC E. coli O157:H7, resuscitation of the VBNC cells during storage (15 days at 7 °C) was not observed. Based on the results obtained, injured L. monocytogenes cells present in the PW are able to be transferred to the product during washing. If VBNC L. monocytogenes cells present in leafy greens (shredded lettuce and baby spinach), they can resuscitate, although cultivable numbers remained very low. Taking all the results together, it could be concluded that under industrial conditions, VBNC cells can be transferred from water to product during washing, but their capacity to resuscitate in the leafy greens during storage is low. Highlights: Viable but non-cultivable (VBNC) cells can cross-contaminate leafy greens during washing. Only a low proportion of L. monocytogenes VBNC cells present in PW were transferred to leafy greens. The transfer of E. coli O157:H7 VBNC cells during washing was not demonstrated. During storage, L. monocytogenes VBNC cells on the product were able to resuscitate. Potential growth of L. monocytogenes VBNC cells during storage of the fresh produce is low.